Lily bush-cricket Tylopsis lilifolia (Orthoptera, Tettigoniidae) color forms eco-geographical distribution analysis (peculiarities identified through Internet resources analysis) - Ozerski, Pavel V. (Ecologica montenegrina, 2025)
The eco-geographical distribution of color forms of the lily bush-cricket Tylopsis lilifolia (Orthoptera, Tettigonioidea) was studied using a novel approach based on the analysis of georeferenced photographic materials from open-access online sources (GBIF and iNaturalist). Images of more than 1,700 adult individuals of T. lilifolia from various parts of Europe, Asia Minor, and the Caucasus were analyzed. A comprehensive assessment was conducted to examine how geographic location and climatic characteristics (temperature, precipitation, and bioclimatic variables) influence the distribution of different color forms. The results show that the green form of T. lilifolia is more frequently found in northern regions with cooler and more humid climates, while the brown form predominates in southern regions with hotter and drier climates. Individuals of other color forms occupy an intermediate position between the green and brown forms in terms of climatic preferences. These findings support the use of georeferenced photographic data as an effective tool for studying intraspecific color polymorphism and its ecological and geographical patterns in orthopteran insects.